11c-16=-6-c+12c

Simple and best practice solution for 11c-16=-6-c+12c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11c-16=-6-c+12c equation:


Simplifying
11c + -16 = -6 + -1c + 12c

Reorder the terms:
-16 + 11c = -6 + -1c + 12c

Combine like terms: -1c + 12c = 11c
-16 + 11c = -6 + 11c

Add '-11c' to each side of the equation.
-16 + 11c + -11c = -6 + 11c + -11c

Combine like terms: 11c + -11c = 0
-16 + 0 = -6 + 11c + -11c
-16 = -6 + 11c + -11c

Combine like terms: 11c + -11c = 0
-16 = -6 + 0
-16 = -6

Solving
-16 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7a/=4a-117 | | 6b+3b+14= | | 5n/4=4n-44 | | 5w^2+2w-7=0 | | 54-11x=16+8x | | x+0.75x=91 | | 4w-63=7w/4 | | -11+10p+100=4-10p-11 | | 10x-5=x-2 | | 5z/3=3z-20 | | 5x^2-10=25 | | 24+30x= | | 11z=8+10 | | 7x-5=2(3x+9) | | 3x+5x-3=-19 | | 0.2x(x+3)-4(2x-3)=0.9 | | y+258=-8y-3 | | 7.50+2.50b=12.50 | | (4x-12)/7 | | (X+3)2+(6x)=46 | | 7x=-5+2(3x+9) | | S-12=47 | | y-13=0(x-4) | | 4x-12/7 | | -3.8s-6.92=19.96+2.6s | | -2d-9=d+84 | | 16-2x^2=-10 | | 19-15-18z=-16-19z | | -3.62-15.1d=16.78-14.4d+2.3d | | t-67=-2t-7 | | 14z=266 | | 9x^2+15=15 |

Equations solver categories